2005
DOI: 10.1002/bjs.5053
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium in elderly patients after major abdominal surgery

Abstract: Approximately half of the elderly patients in this study developed POD. Bleeding was found to be an important risk factor for delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
104
6
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 32 publications
3
104
6
3
Order By: Relevance
“…17 Postoperative delirium occurs most often in the first 3 days after surgery, and most cases develop in the first day. 18,19 However, the time of onset and the duration of postoperative delirium are poorly understood; most published studies of hospitalized patients indicate the prevalence of delirium with no reference to the length of hospital stay or incidence. 20 Other than the stress of surgery, the risk factors for delirium in surgical patients most likely do not differ substantially from those in nonsurgical patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…17 Postoperative delirium occurs most often in the first 3 days after surgery, and most cases develop in the first day. 18,19 However, the time of onset and the duration of postoperative delirium are poorly understood; most published studies of hospitalized patients indicate the prevalence of delirium with no reference to the length of hospital stay or incidence. 20 Other than the stress of surgery, the risk factors for delirium in surgical patients most likely do not differ substantially from those in nonsurgical patients.…”
mentioning
confidence: 99%
“…17 However, advanced age, 8,18,19,[21][22][23][24] preexisting impaired cognition, 8,21,22,[25][26][27] use of psychotropic medications, 22,25,26,28 and impaired functional status and sensory deficits 8,21,27,29 are recognized as predisposing factors for postoperative delirium. A diverse array of precipitating factors for delirium have also been identified in surgical patients, including impaired oxygenation, 2,30 abnormal hematological and/or biochemical status, 25,26,[30][31][32] blood loss and replacement, 19,32 and intravenous infusions. 19,25,26,33 These factors also vary according to the type of surgery undertaken.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Delirium is an acute and fluctuating alteration of mental state of reduced awareness and disturbance of attention. POD (Post Operative Delirium) often starts in the recovery room and occurs up to 5 days after surgery [3][4][5]. One investigation [4] found that many patients with POD on the peripheral ward already had POD in the recovery room.…”
Section: Post Operative Deliriummentioning
confidence: 99%
“…Postoperative delirium is associated with a poor outcome, including increased length of stay (LOS) in hospital and in the intensive care unit (ICU) or Post Anesthesia Care Unit (PACU), frequent medical complications, increased costs of care, and increased mortality [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%